CABI Publications 4 Tree-crop interactions: a physiological approach - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Tree-crop interactions: a physiological approach by Chin K Ong and P A Huxley 1996 416pp price UKL25 00 ISBN 0 85198 987 X CAB International, Wallingford, Oxon OX10 8DE, UK